Integration of Religious Moderation Value in Social Science Learning at Madrasah Tsanawiyah - Ferdianus Jelahu; Halida Halida; Fadilla Syahriani (AT-TA'LIM, 2024)
This study aims to examine in depth the integration of religious moderation values in social science education at Madrasah Tsanawiyah in West Sumatra Province, utilizing a mixed-methods approach that combines qualitative and quantitative methodologies to gain a comprehensive understanding of the application of these values. The research sample consisted of 10 Madrasah Tsanawiyah, purposively selected to reflect geographical variations and institutional characteristics. The qualitative approach was employed to explore the perceptions of teachers, principals, and students regarding the implementation of religious moderation through in-depth interviews and classroom observations. Meanwhile, the quantitative approach involved distributing questionnaires to students to measure their understanding of the concept of religious moderation and the effectiveness of its application in learning. The results indicate that the values of religious moderation have begun to be integrated into the social science learning process, although various challenges persist. These challenges include inadequate training for teachers and a lack of curriculum guidelines that explicitly direct the application of religious moderation in teaching. The integration of the findings from both qualitative and quantitative analyses suggests that, while efforts to integrate the values of religious moderation have commenced positively, further support is necessary, particularly in the form of institutional frameworks and resources to enhance teacher training and develop comprehensive curriculum guidelines.